Influence of light and sex on digestibility and coefficient of growth efficacy in rats - Boza, J.; Brügger, F.G.; Varela, G. (Ars Pharmaceutica (Internet), 1965)
We have seen the influence of light on the sexual sphere of animals, specifying the increase in the production of eggs and milk, and the time of appearance of heat in domestic females. W thought that it would be interesting to study the influence of light and sex in parallel in the digestibility, in the growth and on the volume of intake of the animals.